KAJIAN KEAMANAN PANGAN (FORMALIN, GARAM DAN MIKROBIA) PADA IKAN SEPAT ASIN PRODUKSI INDRALAYA - Rinto Rinto; Elmeizi Arafah; Susila Budi Utama (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
The quality and safety of food material was very important for people healthy. Food safety determined by present of material dangerous (physically, chemistry, and microbiology) of food. The purpose of this research was to analyzed food safety (formaldehyde contain, salt, and the present of bacteria) of salt fish. The result showed that salt fish produced and traded in Indralaya was free from formaldehyde. The formaldehyde contain in salt fish was negative. The salt contain in fish was a low salt (13, 4 - 19, 8%). The salt contain standard of salt fish is lower from 20% (SNI 01-0222-1995). The total of bacteria in salt fish was 3, 20 – 3, 92 (Log10). The sensory value of salt fish in producer higher than trader. The conclusion of this research is salt fish from Indralaya is safe to was consume and quality of salt fish in producer higher than trader in Indralaya traditional market.